Significant causes of disputes of final accounts [electronic resource] - Kong, Sio Kah, 1977-; Maizon Hashim; Fakulti Alam Bina (2015)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2015